PENGARUH KECERDASAN EMOSIONAL, KURIKULUM MERDEKA, MANAJEMEN WAKTU, POLA ASUH ORANG TUA, LINGKUNGAN BELAJAR TERHADAP PRESTASI BELAJAR SISWA KELAS VIII PADA MATA PELAJARAN IPS TERPADU DI SMPN 1 BONJOL - Azahra, Yola; Ronald, Jimi; Stevani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to analyze the influence of: 1) emotional intelligence on learning achievement, 2)the Merdeka curriculum on learning achievement, 3)time management on learning achievement, 4)parenting styles on learning achievement, 5)learning environment on learning achievement, 6)the combined influence of emotional intelligence, the Merdeka curriculum, time management, parenting styles, and learning environment on learning achievement. The research was conducted in June 2025. The type of research used in this study is descriptive and associative research. The population of this study is all eighth-grade students at SMPN 1 Bonjol. Sampling technique used is Stratified Random Sampling method by grouping parents' income levels into high and low, with a sample size of 59 students. The data analysis techniques used are descriptive analysis and inductive analysis, assisted by SPSS software. The research results indicate that there are influences: First, emotional intelligence has a significant effect on learning achievement, as evidenced by a coefficient value of -3.032. This coefficient value is significant because the calculated t value of -9.788 is less than the critical t value of 1.67109 and the significance level of 0.000 is less than 0.05. Second, the independent curriculum has a significant effect on learning achievement, as evidenced by a coefficient value of 1.070. This coefficient value is significant because the calculated t value of 7.344 is greater than the critical t value of 1.67109 and the significance level of 0.000 is less than 0.05. Third, time management has a significant effect on learning achievement, as evidenced by a coefficient value of 0.677. This coefficient value is significant because the calculated t value of 4.494 is greater than the critical t value of 1.67109 and the significance level of 0.000 is less than 0.05. The four parenting styles significantly influence learning achievement, indicated by a coefficient value of 0.794 each. This coefficient value is significant because the calculated t is 3.960 > the t table 1.67109 and the significance value is 0.000 < 0.05. The five learning environments significantly affect learning achievement, indicated by a coefficient value of 0.551 each. This coefficient value is significant because the calculated t is 4.730 > the t table 1.67109 and the significance value is 0.000 < 0.05. Additionally, emotional intelligence, the independent curriculum, time management, parenting styles, and learning environments collectively have a significant influence on learning achievement. This is evidenced by a calculated F value of 20.983 > the F table of 2.26 and a significance value of 0.000 < 0.05. To improve learning achievement, it is necessary to enhance emotional intelligence, the independent curriculum, time management, parenting styles, and the learning environments of eighth-grade students at SMPN 1 Bonjol.